ASSET-BASED COMMUNITY DEVELOPMENT BASIC TRAINING TO INCREASE COMMUNITY ECONOMY IN DUKUH DEMPOK VILLAGE, WULUHAN DISTRICT, JEMBER REGENCY - Suharsono, Riyanto Setiawan; Muliasari, Risa Martha; Lestari, Ayu Widia; Libriana, Pratiwi Dwi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The understanding of MSME business actors in Dukuh Dempok Village, Wuluhan District, Jember Regency regarding Asset-Based Community Development is still very minimal. The biggest strength in supporting the welfare of the community is the potential within oneself, the community has been born, lives, and develops so that it has assets. Assets can also come from the surrounding natural conditions and potential. These potentials can certainly be used as assets in a community empowerment strategy. The economic condition of the people in Dukuh Dempok Village, Wuluhan District, Jember Regency is expected to improve with this Asset-Based Community Development strategy. The natural wealth owned by Dukuh Dempok Village, if supported by the strength of Human Resources, can turn a village into a Tourism Village that is busy being visited by tourists. This dedication is expected to bring the results of the existing assets in the development of Dukuh Dempok Village as a Tourism Village which includes human assets, natural assets, economic assets, social assets, physical assets, cultural assets, and spiritual assets. The methods of this service activity are seminars, practices, discussions, and follow-up in the application of Asset-Based Community Development. Community service activities were carried out at the Dukuh Dempok Village Hall, Wuluhan District, Jember Regency. 24 participants attended, consisting of MSMEs, BUMDes, and the community. The participants enthusiastically took part in the seminar. The seminar activities ran smoothly during the implementation. It is hoped that the participants will be able to further develop their business potential and existing potential in the village so that they can get out of various problems, including problems of improving living standards and socio-economic problems.